2022
DOI: 10.1002/2211-5463.13528
|View full text |Cite
|
Sign up to set email alerts
|

Birth of a poly(A) tail: mechanisms and control of mRNA polyadenylation

Abstract: During their synthesis in the cell nucleus, most eukaryotic mRNAs undergo a two‐step 3′‐end processing reaction in which the pre‐mRNA is cleaved and released from the transcribing RNA polymerase II and a polyadenosine (poly(A)) tail is added to the newly formed 3′‐end. These biochemical reactions might appear simple at first sight (endonucleolytic RNA cleavage and synthesis of a homopolymeric tail), but their catalysis requires a multi‐faceted enzymatic machinery, the cleavage and polyadenylation complex (CPAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 142 publications
0
20
0
Order By: Relevance
“…PAP catalyzes the synthesis of poly-A at the 3′ end of RNA, and it is closely related to the development of diseases. Besides, it has been reported that PAP mRNA is overexpressed in breast, pancreatic, colon, and many other cancer cells. Therefore, the analysis of poly-A and the evaluation of PAP’s activity could offer robust biological evidence and work as promising molecular tools for the early diagnosis of cancers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…PAP catalyzes the synthesis of poly-A at the 3′ end of RNA, and it is closely related to the development of diseases. Besides, it has been reported that PAP mRNA is overexpressed in breast, pancreatic, colon, and many other cancer cells. Therefore, the analysis of poly-A and the evaluation of PAP’s activity could offer robust biological evidence and work as promising molecular tools for the early diagnosis of cancers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since the PABPN1 protein controls the poly(A) tail synthesis and length (25), we also investigated if the ZC3H11A protein has an impact on poly(A) tail status using HAdV-5 as a model. Since reliable detection of the poly(A) tails is challenging, we used the PCR-based ePAT detection method, which can detect qualitative changes in the poly(A) tail (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PABPN1 can also define the poly(A) tail length as it mediates interactions between the PAP protein and the cleavage and specificity factor 1 (CPSF1) (22,23). Historically, the PABPN1 protein binding to poly(A) tails was suggested to increase mRNA stability, nuclear mRNA export, and translation (24,25). Surprisingly, PABPN1 also has an opposite role as it can promote the turnover of some of the non-coding snoRNA host gene (SNHG) transcripts (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the polyadenylation site involves a complex interplay between polyadenylation signal sequences surrounding the CPA site, as well as pre-mRNA 3’ end processing protein complexes which recognize these motifs [Zhang et al . 2021, Rodríguez-Molina and Turtola 2023]. The plant polyadenylation signal consists of three weakly conserved sequence regions: Far Upstream Element (FUE), Near Upstream Element (NUE), and Cleavage Element (CE) [Hunt 2008, Xing and Li 2011].…”
Section: Introductionmentioning
confidence: 99%